2009
DOI: 10.1007/s11999-009-0724-y
|View full text |Cite
|
Sign up to set email alerts
|

Time of Return of Elbow Motion after Percutaneous Pinning of Pediatric Supracondylar Humerus Fractures

Abstract: The most common treatment for displaced pediatric supracondylar humerus fractures is closed reduction and percutaneous pinning. However, the time for return of elbow motion after treatment of these injuries is not well documented. To describe the return of elbow motion after closed reduction and percutaneous pinning of these fractures we retrospectively reviewed 63 patients (age range, 1.6-13.8 years) with displaced supracondylar fractures of the humerus stabilized with either two or three lateral entry pins. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 19 publications
2
30
0
5
Order By: Relevance
“…Although sagittal alignment of pediatric SCH fractures has not received the same attention as coronal alignment in the literature, malalignment in this plane can result in substantial limitations in function, elbow flexion, and range of motion at union and skeletal maturity. [23][24][25][26][27] In a study of 223 SCH fractures of all types, Simanovsky et al 23 found 13% with extension malunion (humerocapitellar angle <35 degrees). Of those patients, 50% had limited elbow flexion; 31% were aware of that limitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sagittal alignment of pediatric SCH fractures has not received the same attention as coronal alignment in the literature, malalignment in this plane can result in substantial limitations in function, elbow flexion, and range of motion at union and skeletal maturity. [23][24][25][26][27] In a study of 223 SCH fractures of all types, Simanovsky et al 23 found 13% with extension malunion (humerocapitellar angle <35 degrees). Of those patients, 50% had limited elbow flexion; 31% were aware of that limitation.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have suggested that malalignment in the sagittal plane can result in substantial limitations in function, elbow flexion, and range of motion at union and skeletal maturity. [23][24][25][26][27] The retrospective nature of our study also precluded obtaining standardised radiographs postoperatively or at final follow-up. Although humeral rotation at the time of radiography can lead to alterations in measurement of the Baumann angle and the AHL, 30,31 these inconsistencies should be similarly dispersed within each pin size group.…”
Section: Discussionmentioning
confidence: 99%
“…Percutaneous pinning is a popular method of choice for supracondylar fractures [6][7][8] and has been reported to be a safe and cost-effective method that provides good functional results [7][8][9][10]. Even dislocated supracondylar fractures can be treated by repositioning and casting with an excellent functional outcome [11].…”
Section: Introductionmentioning
confidence: 99%
“…Supracondylar humeral fractures are the most common elbow fractures in children, and two recent studies documented a gradual return to full motion within one year after the injury in almost all patients 82,83 . Motion rapidly returns to 75% of that in the contralateral elbow within the first months and may be slower in children who have surgical management or who are older.…”
Section: Traumamentioning
confidence: 99%